Kekuatan Pembuktian Alat Bukti Elektronik Berdasarkan Undang-Undang Nomor 19 Tahun 2016 Tentang Informasi Transaksi Elektronik (ITE) - Taufik Iskandar; Mauluddin Mauluddin; Rudi Rudi; Marsudi Utoyo (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2023)
E-commerce is a trade transaction that allows buying and selling without having to meet directly between the seller and the buyer. This trading system requires a strong sense of trust between one another, between sellers and buyers. Recognition of electronic evidence as evidence that can be submitted to court and recognized as valid evidence has been carried out since 1977 through the Company Documents Act which stipulates that microfilm containing recordings of company documents can be submitted as evidence in court if it arises in the future. lawsuit. According to the Company Documents Law, electronic document evidence is part of documentary evidence, while the Corruption Law explicitly explains that electronic information and electronic documents are an extension of demonstrative evidence. Because electronic letters in the form of electronic information or electronic documents have been recognized as one of the legal means of evidence in special crimes outside the Criminal Code, parallel to the legal evidence in Article 184 of the Criminal Procedure Code, which is a new type of evidence, it is hoped that investigators, public prosecutors, advisers law and judges have an understanding of this electronic evidence. In examining criminal cases, it is hoped that the judge will impose a sentence based on two valid pieces of evidence and the judge will gain confidence that it is the defendant who is guilty of committing a crime, so the judge must impose the maximum sentence according to the prosecutor's demands, so that the defendant becomes deterrent and the community's sense of justice is fulfilled.